Evaluation of Salivary Interleukin 6 and MicroRNA 146a in Patients with Chronic Periodontitis and Their Association with Periodontal Parameters - Suha Khaleel Ibrahim; Ghada Bouslama; Lamia Oualha (Dentistry 3000)
Objective: The aim of this study was to evaluate of the role of interleukin 6 (IL-6) and microRNA 146a (miRNA 146a) in chronic periodontitis (CPD).